2022
DOI: 10.48550/arxiv.2203.00221
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hitting a New Low: The Unique 28 h Cessation of Accretion in the TESS Light Curve of YY Dra (DO Dra)

Katherine L. Hill,
Colin Littlefield,
Peter Garnavich
et al.

Abstract: We present the Transiting Exoplanet Surveying Satellite (TESS ) light curve of the intermediate polar YY Draconis (YY Dra, also known as DO Dra). The power spectrum indicates that while there is stream-fed accretion for most of the observational period, there is a day-long, flat-bottomed low state at the beginning of 2020 during which the only periodic signal is ellipsoidal variation and there is no appreciable flickering. We interpret this low state to be a complete cessation of accretion, a phenomenon that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The SAP light curve of Paloma shows a gentle parabolic curvature, while the PDCSAP light curve lacks any overall trend. To determine which light curve to use, we follow the general approach of Hill et al (2022) and compare both the SAP and PDCSAP light curves against simultaneous r-band photometry from the Zwicky Transient Facility (ZTF; Bellm et al 2019). We used linear regressions to compare the flux of the seven available ZTF observations with the simultaneous TESS observations and found that the PDCSAP light curve agreed well with the ZTF data, with a coefficient of determination of r 2 P DCSAP = 0.54.…”
Section: The Tess Observation Of Palomamentioning
confidence: 99%
“…The SAP light curve of Paloma shows a gentle parabolic curvature, while the PDCSAP light curve lacks any overall trend. To determine which light curve to use, we follow the general approach of Hill et al (2022) and compare both the SAP and PDCSAP light curves against simultaneous r-band photometry from the Zwicky Transient Facility (ZTF; Bellm et al 2019). We used linear regressions to compare the flux of the seven available ZTF observations with the simultaneous TESS observations and found that the PDCSAP light curve agreed well with the ZTF data, with a coefficient of determination of r 2 P DCSAP = 0.54.…”
Section: The Tess Observation Of Palomamentioning
confidence: 99%